2005
DOI: 10.1063/1.1929889
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth and characteristics of N-doped anatase TiO2 films grown using a free-radical nitrogen oxide source

Abstract: This paper reports on a systematic investigation of nitrogen (N) doping in single-crystalline TiO2 films possessing an anatase phase. TiO2 films heavily doped with N were grown with high crystallinity by employing a pulsed laser ablation technique using a close lattice-matched LaAlO3 (100) substrate and NO as the source gases for N doping. N15 and O18 isotope tracing by secondary-ion-mass spectroscopy confirmed that N and O atoms were simultaneously incorporated into the films as a consequence of the gas phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 53 publications
5
26
0
Order By: Relevance
“…The N doping in TiO 2 lattice can be easily introduced by the formation of oxygen deficiency in the TiO 2 [3,7] (the oxygen sites is partially replaced with N atoms while TiO 2 is simultaneously reduced [48]). The N doping often causes a shift of transmission band-edge toward a visible light range and expansion of cellvolume (the N 3− anion (0.171 nm) is larger than the O 2− anion (0.132 nm)) [49,50], which is consistent with our results. When considered from the atomic concentrations, the unit cell volumes, and the optical properties (especially the large red shift of the transmission edge for some samples compared with non-doped O-1 sample), the W-1, 2, 3 samples should contain high (excessive) concentration of N (atoms) in anatase TiO 2 lattice.…”
Section: Discussionsupporting
confidence: 93%
“…The N doping in TiO 2 lattice can be easily introduced by the formation of oxygen deficiency in the TiO 2 [3,7] (the oxygen sites is partially replaced with N atoms while TiO 2 is simultaneously reduced [48]). The N doping often causes a shift of transmission band-edge toward a visible light range and expansion of cellvolume (the N 3− anion (0.171 nm) is larger than the O 2− anion (0.132 nm)) [49,50], which is consistent with our results. When considered from the atomic concentrations, the unit cell volumes, and the optical properties (especially the large red shift of the transmission edge for some samples compared with non-doped O-1 sample), the W-1, 2, 3 samples should contain high (excessive) concentration of N (atoms) in anatase TiO 2 lattice.…”
Section: Discussionsupporting
confidence: 93%
“…The N doping often causes the shift in the transmission band-edge toward the visible light range and the cell-volume expansion (the N 3À anion (0.171 nm) is larger than the O 2À anion (0.132 nm)), 11,26) both of which are observed in our results. When considered from the atomic concentrations, the unit cell volumes and the optical properties, the A-2 and A-3 samples should contain high concentration of N atoms in the TiO 2 anatase phase with high oxygen deficiency.…”
Section: Discussionsupporting
confidence: 76%
“…The origin of the N 1s peak components in N-doped TiO2 has been much discussed in the literature. However, it is generally accepted that a N component at approximately 396 eV corresponds to N substituted for O in the TiO2 phase [12,[51][52][53][54][55][56][57][58][59]. It has recently been shown that a peak at approximately 400 eV is observed on many surfaces due to the presence of Ncontaining organic contamination [60], but a peak can also occur at a similar binding energy due to the presence of interstitial NO species [51,54,[61][62][63][64].…”
Section: Alumina Membranementioning
confidence: 99%